Traduire le « vertige de l’expansion » - Laura Santone (Flaubert: Revue Critique et Génétique)
With a comparative approach connecting four Italian translations of Madame Bovary, this article analyzes, through the translators’ various choices, the “expansion vertigo” that pervades the novel’s verbal representation by inscribing a depth that unfolds on the verticality axis. The selected passages are structured around a paradigm that evokes the color “blue”, a chromatic presence that in all its shades envelops Emma’s life. Looking at the Italian editions and studying more closely these “secondary” texts, we realize that a translation can be “a moment of a text in motion” (Meschonnic), an experience of an energeia fertilizing writing and even language.